Strategy for Developing Processed Fishery and Marine Products in Bontang City Through Regional Research And Innovation (RID) Ecosystem Approach - Yogi Octavian Murdiono Putra; A Faroby Falatehan; Feryanto Feryanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study, entitled Strategy for Developing Processed Fishery and Marine Products in Bontang City through the Regional Research and Innovation (RID) Ecosystem Approach, analyzes strategies for strengthening marine-based regional economic potential in an extractive-industry-dependent region. The research aims to identify strategic directions for developing processed fishery and marine products as a leading sector to support economic diversification in Bontang City. The study employs a mixed qualitative–quantitative approach using the Regional Research and Innovation ecosystem framework, which examines six elements: policy and infrastructure, institutional capacity, partnerships, innovation culture, regional integration, and global alignment. Data were collected through Focus Group Discussions with regional stakeholders and analyzed using Standard Gap Analysis with a Likert scale and SWOT analysis. The results reveal substantial gaps between current and expected ecosystem conditions. Based on these findings, nine strategic initiatives are proposed to strengthen institutional capacity, innovation support, and collaborative partnerships for sustainable fisheries-based regional economic development.